ANALISIS DAN EVALUASI IMPLEMENTASI PENGELOLAAN KEPEMILIKAN UMUM DAN NEGARA DI INDONESIA (PENDEKATAN MADZHAB HAMFARA) - Siti Murtiyani; Hery Sasono; Dwi Condro Triono; Hanifah Zahra (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2016)
This study aims to analyze and critically evaluate the implementation of the management of public ownership (Milkiyah 'ammah) and State ownership (Milkiyah Daulah) in Indonesia. This study descriptively describes the implementation of both ownerships that are currently practicing in Indonesia. Theoretical approaches used is the Islamic Economic System Madzhab Hamfara (Hadza Min fadzli Rabbi) who critically evaluate the implementation of the public wealth management and state wealth in Indonesia. This research used secondary data that was obtained from Madzhab Hamfara books, literature, journal and information relating to the Indonesian State assets management system. A comparative analysis was conducted to understand the difference between the public wealth management and state wealth management in Indonesia. Findings show that the management of both, public and state ownership are not in accordance to the ownership management approach of Madzhab Hamfara Islamic Economic System. The evidence suggests that both public and state ownership are not fully managed by the Government of Indonesia. The fact shows that public ownership in the form of water, fire and pastures are managed by individuals and institutions as well as foreign parties who have fund to privatize the public ownership. Consequently, it has the impact on unequal distribution of income that cause poverty in Indonesia. This research suggest that government should implement Islamic Economic System Madzhab Hamfara in managing public and state ownership in Indonesia. =========================================== Kajian ini bertujuan untuk menganalisis dan mengevaluasi secara kritis penerapan pengelolaan kepemilikan umum (Milkiyah 'Ammah) dan kepemilikan negara (Milkiyah Daulah) di Indonesia. Studi ini menjelaskan secara deskriptif tentang implementasi pengelolaan kedua kepemilikan tersebut yang sekarang dipraktikkan di Indonesia. Teori yang digunakan dalam penelitian ini adalah Sistem Ekonomi Islam Madzhab Hamfara (Hadza Min fadzli Rabbi) yang secara kritis mengevaluasi implementasi pengelolaan kepemilikan umum dan negara di Indonesia. Kajian ini menggunakan data sekunder yang berasal buku-buku madzhab Hamfara, literatur, artikel jurnal dan informasi lainnya yang terkait dengan pengelolaan aset di Indonesia. Analisis perbandingan juga dilakukan untuk memahami perbedaan pengelolaan kepemilikan umum dan kepemilikan negara. Hasil kajian menunjukkan bahwa pengelolaan kepemilikan, baik kepemilikan umum maupun negara di Indonesia, tidak dijalankan sesuai dengan sistem ekonomi Islam Madzhab Hamfara. Bukti-bukti menunjukkan bahwa pengelolaan kepemilikan publik dan negara tidak sepenuhnya dilakukan oleh negara. Fakta juga menunjukkan bahwa kepemilikan tersebut lebih banyak diserahkan kepada lembaga-lembaga privat bahkan lembaga-lembaga asing. Akibatnya, kesenjangan pendapatan yang menjadi pemicu kemiskinan terus terjadi. Kajian ini menyarankan agar pemerintah mengimplementasikan sistem ekonomi Islam Madzhab Hamfara dalam pengelolaan kepemilikan umum dan negara di Indonesia.